THE INFLUENCE OF CONSUMER BEHAVIOR AND SHARIA FINANCIAL LITERACY ON INTEREST IN USING FINTECH P2P LENDING AMONG FEBI UINSU STUDENTS - Hayati, Nur Fadillah; Anggraini, Tuti; Nasution, Muhammad Latief Ilhamy (Jurnal Pamator : Jurnal Ilmiah Universitas Trunojoyo, 2025)
This study aims to analyze the effect of consumptive behavior and Islamic financial literacy on the interest in using fintech P2P lending among students of the Faculty of Islamic  Economics and Business (FEBI) at UINSU. This research employs a quantitative approach with a causal associative method. The population consists of active FEBI UINSU students from the 2021 cohort, with a sample of 100 respondents selected using puprosive sampling. Data were collected through questionnaires and analyzed using multiple linear regression with partial (t) tests and simultaneous (F) tests. The results indicate hat consumptive behavior has a positive and significant effect on the interest in using fintech P2P lending. Islamic financial literacy also has a positive and significant effect on this interest. Simultaneously, both independet variables significantly influence students interest in using conventional fintech. This phenomenon shows that although students have a good understanding of Islamic financial principles, factors such as accessibility, service speed, limited availability of Islamic fintech, and consumptive behavior still lead them to use conventional fintch.Keywords: Consumptive Behavior, Islamic Financial Literacy, Interest, Fintech P2P Lending